Estimating the Risk of Re-Emergence after Stopping Polio Vaccination - Sasaki, Akira; Haraguchi, Yoshihiro; Yoshida, Hiromu (Frontiers in Microbiology, 2012)
Live vaccination against polio has effectively prevented outbreaks in most developed countries for more than 40 years, and there remain only a few countries where outbreaks of poliomyelitis by the wild strain still threaten the community. It is expected that worldwide eradication will be eventually achieved through careful surveillance and a well-managed immunization program. The present paper argues, however, that based on a simple stochastic model the risk of outbreak by a vaccine-derived strain after the cessation of vaccination is quite high, even if many years have passed since the last confirmed case. As vaccinated hosts are natural reservoirs for virulent poliovirus, the source of the risk is the vaccination itself, employed to prevent the outbreaks. The crisis after stopping vaccination will emerge when the following two conditions are met: the susceptible host density exceeds the threshold for epidemics and the vaccinated host density remains large enough to ensure the occurrence of virulent mutants in the population. Our estimates for transmission, recovery, and mutation rates, show that the probability of an outbreak of vaccine-derived virulent viruses easily exceeds 90%. Moreover, if a small fraction of hosts have a longer infectious period, as observed in individuals with innate immunodeficiency, the risk of an outbreak rises significantly. Under such conditions, successful global eradication of polio is restricted to a certain range of parameters even if inactive polio vaccine (IPV) is extensively used after the termination of live vaccination.